Trade-offs between justices, economics, and efficiency - Stefan Baumgärtner; Stefanie Glotzbach; Nikolai Hoberg; Martin F. Quaas; Klara Stump (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2011)
We argue that economics - as the scientific method of analyzing trade-offs - can be helpful (and may even be indispensable) for assessing the trade-off between intergenerational and intragenerational justice. Economic analysis can delineate the opportunity set of politics with respect to the two normative objectives of inter- and intragenerational justice, i.e. it can describe which outcomes are feasible in achieving the two objectives in a given context, and which are not. It can distinguish efficient from inefficient uses of instruments of justice. It can identify the opportunity cost of attaining one justice to a higher degree, in terms of less achievement of the other. We find that, under very general conditions, (1) efficiency in the use of instruments of justice implies that there is rivalry between the two justices and the opportunity cost of either justice is positive; (2) negative opportunity costs of achieving one justice exist if there is facilitation between the two justices, which can only happen if instruments of justice are used inefficiently; (3) in outcomes of inefficient uses of instruments of justice in the interior of the opportunity set, the two justices are independent of each other and the opportunity cost of either justice is zero.
Keywords: A13; D61; D63; 330; economics; efficiency; intragenerational and intergenerational justice; normative objectives; opportunity set; opportunity cost; scarce resources; Gerechtigkeit; Generationenbeziehungen; Soziale Gerechtigkeit; Sozialpolitik; Wirkungsanalyse; Opportunitätskosten; Theorie